Reversible photo-induced isomerization of cis-[M(L-κS,O)2] (M=PdII, PtII) complexes with N,N-dialkyl-N’-acyl(aroyl)thiourea ligands (HL): Key to the isolation of novel geometric trans-[M(L-κS,O)2] and trans-[M(L-κS,N)2] isomers - Nkabyo, Henry Ane (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.